74.6k views
2 votes
For the function p defined by p(m)=2m2−4m+3, find p(13).

For the function p defined by p(m)=2m2−4m+3, find p(13).-example-1

2 Answers

1 vote

Answer:


(17)/(9)

Explanation:


2\left((1)/(3)\right)^2-4\left((1)/(3)\right)+3


2\left((1)/(9)\right)-4\left((1)/(3)\right)+3


(2)/(9)-(4)/(3)+3


(2)/(9)-(4)/(3)+(3)/(1)


(2)/(9)-(4 * 3)/(3 * 3)+(3 * 9)/(1 * 9)


(2)/(9)-(12)/(9)+(27)/(9)


(2-12+27)/(9)


=(17)/(9)

User Alex Klaus
by
5.7k points
2 votes

Answer:

Option C

Explanation:

=> p(m) =
2m^2-4m+3

Putting m =
(1)/(3)

=> p(1/3) =
2((1)/(3))^2-4((1)/(3) )+3

=> p(1/3) =
(2)/(9)-(4)/(3) +3

=> p(1/3) =
(2-12+27)/(9)

=> p(1/3) =
(17)/(9)

User Paridokht
by
5.4k points